Moral and ethical aspect of distance education - Nuriet Karpushevna Gubzhokova (Вестник Майкопского государственного технологического университета, 2023)
Distance learning has been one of the integral trends in the development of the modern educational system, representing a set of new ways of transferring information, innovative methods of interaction between teachers and students. Distance education, which has emerged as a way of providing equal opportunities to all potential participants in the educational process, is a source of new problems, which predetermines the relevance of the research. The purpose of the research is to identify the most important moral and ethical problems, including those that have worsened during the COVID-19 pandemic, which has become a serious challenge for the global educational system. The research methods used are analysis, analogy, generalization. The experience of remote work of MSTU teachers in the pandemic period is also in demand. The results: the article highlights the main ethical threats associated with online education, which are distributed according to the nature and degree of impact on the learning process. The key findings: the moral and ethical aspect of distance education is one of the most important in the gradual transition to a new teaching format. These problems became especially acute in the situation of the COVID-19 pandemic, during which the forced and accelerated introduction of distance learning into pedagogical practice has been carried out, which revealed the vulnerability of entire regions and categories of the population. The experience of the education system in the pandemic requires deep study and generalization to adjust the methods and rates of innovative processes in modern Pedagogy, as well as to clarify the place, nature and importance of distance learning in the educational system.